The effect of oil palm decanter cake on the accumulation of nutrients and the stomatal opening of Solanum melongena (brinjal) plants - A. Embrandiri; Parveen Fatemeh Rupani; Sultan Ahmed Ismail; Rajeev Pratap Singh; M. Hakimi Ibrahim; Mohd. Omar B. Abd. Kadir (International Journal of Recycling of Organic Waste in Agriculture, 2024)
Purpose Research has shown that oil palm decanter cake (DC) serves as a potential source of nutrients for plant growth. This study therefore investigated the applicability of decanter cake (DC) as an amendment to soil for the growth of Solanum melongena (brinjal) at three ratios 10, 20, 30 % DC and suitable controls (0 %). Methods Seeds of brinjal were sown in soils amended with decanter cake at 10, 20, 30 % w/w and 0 % as control. Nutrient enrichment factors were calculated from the concentration of selected metals (Cu, Ca, Fe, Zn and Mg) in plant parts. The scanning electron micrographs were also taken to measure the stomatal opening/closing due to the effect of excess nutrients on the leaf structure. Results Enrichment factor (EF) values in this study were all below 3 indicating low enrichment of metal ions from soil to plants. SEM studies of the leaf epidermis of the test plants revealed the closure of guard cells with increasing decanter cake treatments. Conclusions Decanter cake at 20 % amendments with soil could serve as a source of soil amendment for cultivation of S. melongena plants.